Cost and Benefit Analysis of RSPO Certification (Case Study in PT BCA Oil Palm Plantation in Papua) - Faris Salman; Mukhamad Najib; Setiadi Djohar (Indonesian Journal of Business and Entrepreneurship (IJBE), 2017)
RSPO is sustainable. It is one of many certification labels to justify a sustainable palm oil practice. The objective of this study is to identify monetary benefit and cost with the existing operating scenario of the company, or if the company is registered as the RSPO member. To identify the benefit or cost that might occur, this research compared the NPV, IRR, and benefit-cost ratio among the alternative scenarios. An ex-ante projective cash flow is simulated using the company’s historical financial report from year 2012-2016 to obtain monetary perspective of the amount of money required by the plantation to proceed with certification. Certification should cost the plantation around 466 billion rupiahs with only 66 billion rupiahs of additional income from CPO premium if the company is able to complete its certification by 2019. Total benefit of income obtained from selling the certified products of CPO and PKO may cover the certification expense which does not exceed the cost paid with the discrepancy of 331 billion rupiahs. This amount can be used to establish another palm oil plantation, create jobs and contribute to domestic products. However, the net monetary loss is close to the value obtained from timber upon land clearing, which was at 286 billion rupiahs. Being sustainable is probably never about monetary value but more about the responsibility of managing the sustainable oil palm plantation and the environment that must be taken care of.Keywords: RSPO, oil palm plantation, cost and benefit analysis, oil palm in Papua, RSPO finansial benefit